Implementing sustainability in laboratory activities: A case study on aluminum titanium nitride based thin film magnetron sputtering deposition onto commercial laminated steel. (20th February 2021) - Fiameni, Stefania; Battiston, Simone; Castellani, Valentina; Barison, Simona; Armelao, Lidia
Abstract: The goal of the study was to identify the environmental hotspots of an experimental research work at lab scale consisting in the physical vapor deposition magnetron sputtering of aluminum titanium nitride based thin coatings onto commercial laminated steel. The findings can provide useful insights for supporting the design of future experimental research campaigns, or instrumentation set-ups, with lower environmental impacts. Results highlighted that the main driver of impacts in the analyzed laboratory activities was the electricity used for instruments operations, in particular for the vacuum keeping. Thus, several optimization strategies were evaluated to reduce the overall electricity consumption, and to improve the environmental profile of experimental activities. Graphical abstract: Image 1 Highlights: LCA of laboratory activites on PVD magnetron sputtering deposition films. Main driver of impacts was the electricity used for instrumental operations. Several instrumental set-ups were analyzed, to identify the less impacting one. The vacuum system resulted to be a hotspot in terms of electricity use. The use of a pre-chamber is the most promising solution to reduce impacts.